Pediatric Targeted Therapy: Clinical Feasibility of Personalized Diagnostics in Children with Relapsed and Progressive Tumors. (26th November 2015) - Selt, Florian; Deiß, Alica; Korshunov, Andrey; Capper, David; Witt, Hendrik; van Tilburg, Cornelis M.; Jones, David T. W.; Witt, Ruth; Sahm, Felix; Reuss, David; Kölsche, Christian; Ecker, Jonas; et al.
Abstract: The "pediatric targeted therapy" (PTT) program aims to identify the presence and activity of druggable targets and evaluate the clinical benefit of a personalized treatment approach in relapsed or progressive tumors on an individual basis. 10 markers (HDAC2, HR23B, p‐AKT, p‐ERK, p‐S6, p‐EGFR, PDGFR‐alpha/beta, p53 and BRAFV600E) were analyzed by immunohistochemistry. Pediatric patients with tumors independent of the histological diagnosis, with relapse or progression after treatment according to standard protocols were included. N  = 61/145 (42%) cases were eligible for analysis between 2009 and 2013, the most common entities being brain tumors. Immunohistochemical stainings were evaluated by the H ‐Score (0–300). In 93% of the cases potentially actionable targets were identified. The expressed or activated pathways were histone deacetylase (HDACs; 83.0% of cases positive), EGFR (87.2%), PDGFR (75.9%), p53 (50.0%), MAPK/ERK (43.3%) and PI3K/mTOR (36.1%). Follow‐up revealed partial or full implementation of PTT results in treatment decision‐making in 41% of the cases. Prolonged disease stabilization responses in single cases were noticed, however, response rates did not differ from cases treated with other modalities. Further studies evaluating the feasibility and clinical benefit of personalized diagnostic approaches using paraffin material are warranted.